The KGRAM Abstract Machine for Knowledge Graph Querying - Corby, Olivier; Zucker, Catherine Faron (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
In this paper we present the KGRAM abstract machine dedicated to querying knowledge graphs. It is the result of an abstraction process we performed to reach a generic solution to the problem of querying graphs in various models. We identified high level abstract primitives that constitute the expressions of the query language and the interfaces of KGRAM for both its data structures and its operations.